2011
DOI: 10.5021/ad.2011.23.s2.s155
|View full text |Cite
|
Sign up to set email alerts
|

Primary Malignant Rhabdoid Melanoma

Abstract: Melanoma with rhabdoid features is an uncommon variant of malignant melanoma. Here, we describe a rare case of primary rhabdoid malignant melanoma. A 54-year-old man presented with a black tumor measuring 3×4 cm on the right forearm. Histologic sections showed a tumor mass with rhabdoid features composed entirely of polygonal neoplastic cells with eccentric nuclei, prominent nucleoli, and large hyaline cytoplasmic inclusions. The tumor cells were immunoreactive with HMB-45, S100, Fontana-Masson silver and vime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…[5][6][7] So far, to the best of our knowledge, only seven cases showing primary malignant rhabdoid melanomas have been described. 3,5 Diagnosis of cases without conventional histopathological features of melanoma is extremely challenging, especially due to the absence of melanin pigment, focal and very weak positivity of S100 protein and negativity for HMB-45 and MelanA. 8 The immunoprofile of our case is rather similar to that of previously reported cases.…”
supporting
confidence: 72%
See 2 more Smart Citations
“…[5][6][7] So far, to the best of our knowledge, only seven cases showing primary malignant rhabdoid melanomas have been described. 3,5 Diagnosis of cases without conventional histopathological features of melanoma is extremely challenging, especially due to the absence of melanin pigment, focal and very weak positivity of S100 protein and negativity for HMB-45 and MelanA. 8 The immunoprofile of our case is rather similar to that of previously reported cases.…”
supporting
confidence: 72%
“…1 In 1992 the rhabdoid variant of melanoma was first described by Bittesini et al 2 It is considered an extremely rare variant of malignant melanoma, better observed in metastatic cases than in primary melanomas. 3 Histopathologically it is characterized by the presence of large sheets or nests of polygonal tumour cells with abundant cytoplasm containing eosinophilic inclusions and a peripherally located nucleus. 4 An 80-year-old man, without relevant past dermatological history, presented to us with multiple reddish rapidly growing nodules on his forehead.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Rhabdoid melanoma was first described by Bittesini et al in 1992 [ 1 ]. Since then, over 40 cases of metastatic or recurrent rhabdoid melanoma have been reported, but only 7 cases of PRM appear in the literature [ 4 , 5 , 6 , 7 , 8 ]. Here we report the first Japanese case of PRM in English.…”
Section: Discussionmentioning
confidence: 99%
“…It may acquire spindle cell morphology, which is designated as sarcomatoid differentiation and it may acquire rhabdoid features, which is designated as rhabdoid differentiation 1 . Rhabdoid features was described in other malignancies including carcinomas, 2 melanoma, 3 and sarcomas. 4,5 Cohesive epithelioid cells with eccentric vesicular nuclei, prominent nucleoli and intracytoplasmic hyaline esinophilic globules are the main features of rhabdoid cells 6 .…”
Section: Introductionmentioning
confidence: 99%